The reaction of an iridium PNP complex with parahydrogen facilitates polarisation transfer without chemical change. Issue 3 (20th November 2014) - Holmes, Arthur J.; Rayner, Peter J.; Cowley, Michael J.; Green, Gary G. R.; Whitwood, Adrian C.; Duckett, Simon B.
Abstract : The pincer complex [(C5 H3 N(CH2 P( t Bu)2 )2 )Ir(H)2 (py)]BF4 is shown to be active for signal amplification by reversible exchange. Abstract : The short lived pincer complex [(C5 H3 N(CH2 P( t Bu)2 )2 )Ir(H)2 (py)]BF4 is shown to be active for signal amplification by reversible exchange. This catalyst formulation enables the efficient transfer of polarization from para hydrogen to be placed into just a single molecule of the hyperpolarisation target, pyridine. When the catalysts 1 H nuclei are replaced by 2 H, increased levels of substrate hyperpolarization result and when the reverse situation is examined the catalyst itself is clearly visible through hyperpolarised signals. The ligand exchange pathways of [(C5 H3 N(CH2 P( t Bu)2 )2 )Ir(H)2 (py)]BF4 that are associated with this process are shown to involve the formation of 16-electron [(C5 H3 N(CH2 P( t Bu)2 )2 )Ir(H)2 ]BF4 and the 18-electron H2 addition product [(C5 H3 N(CH2 P( t Bu)2 )2 )Ir(H)2 (H2 )]BF4 .